A designed miniature sensor for the trace level detection and degradation studies of the toxic dye Rhodamine B. Issue 25 (23rd May 2022) - Hayat, Mazhar; Shah, Afzal; Hakeem, Muhammad Kamran; Irfan, Muhammad; Haleem, Abdul; Khan, Sher Bahadar; Shah, Iltaf
Abstract : The presence of organic pollutants in water and food samples is a risk for the environment. Abstract : The presence of organic pollutants in water and food samples is a risk for the environment. To avoid this hazard a variety of analytical tools are used for the detection of toxic organic contaminants. Herein we present a selective and sensitive electrochemical sensor based on amino group functionalized multi walled carbon nanotubes and carboxylic group functionalized multi walled carbon nanotubes (HOOC- f MWCNTs/NH2 - f MWCNTs) as modifiers of the glassy carbon electrode for the detection of a toxic dye, Rhodamine B. The sensing ability of the designed sensor was examined by electrochemical impedance spectroscopy, cyclic voltammetry and square wave voltammetry. The synergistic effect of HOOC- f MWCNTs and NH2 - f MWCNTs (layer by layer) led to enhanced electrocatalytic activity of the modified electrode surface for Rhodamine B detection. Under optimized conditions, the graph between concentration and peak current followed a linear trend in the concentration range of 0.1 nM to 0.05 μM. The limits of detection and quantification were found to be 57.4 pM and 191.3 pM respectively. The designed sensor was also used for probing the degradation of Rhodamine B. Sodium borohydride was found to degrade Rhodamine B in neutral media under ambient conditions. The kinetics of degradation followed first order kinetics. Rhodamine B degraded to the extent of more than 80% as revealed by electrochemical and spectrophotometric techniques. The developed method is promising for the treatment of dye contaminated wastewater. Moreover, it uses only a microliter volume of the sample for analysis.